Prevalence of green mussels (Perna viridis) parasites in Randusanga Kulon, Brebes - Puspitasari, Hesti; Sanjayasari, Dyahruri (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Green mussels are one of the food ingredients that are popular with the public because of their good nutritional content for the body and affordable prices. Green mussels are also a cultivation commodity that is easy to develop for coastal communities, especially coastal communities in the Randusanga Kulon Waters, Brebes. One of its characteristics, which is living sedentarily and being a filter feeder, makes green mussels easily infected with parasites and polluting organisms. Therefore, this study aims to determine the prevalence of parasites in green mussels (Perna viridis) in the Randusanga Kulon, Brebes. Parasite analysis in green mussels was carried out in July 2023 using the random sampling method. This study used green mussel samples with an average length of 12.03 ± 1.02 cm. Observations of endoparasites were carried out on the legs, gills, and contents of the digestive tract, while observations of ectoparasites were carried out on the shells of green mussels. Observations were carried out on 7 (seven) samples of green mussels with 3 (three) repetitions in each part observed. Based on observations, parasites were found with a prevalence category of often to always with prevalence values ranging from 14.3% -100%. The types of parasites found were Perkinsus sp., Balanus sp., Ciliata, Strongyloides stercoralis, Strongyloides papillosus.